Agility in Action. (Manufacturing Engineering)
Navistar Engine Group adapts one of its diesel engine plants in Huntsville, AL, to manufacture 125,000 engines a year in many variations of two block configurations-and with a lot size of one. It may be the world's only engine plant that manufactures V-block and I-block engines on the same line. Not only has flexibility gone up, quality has shown improvement as well.